17β-Estradiol alters oxidative damage and oxidative stress response protein expression in the mouse mammary gland. (5th May 2016) - Yuan, Lisi; Dietrich, Alicia K.; Ziegler, Yvonne S.; Nardulli, Ann M.
Abstract: Although substantial evidence has demonstrated that parity and 17β-estradiol (E2) reduce mammary carcinogenesis, it is not clear how this protection is conferred. Thus, we examined the effects of parity and E2 treatment in the mammary glands of ovariectomized 15 week-old virgin mice, 15 week-old primiparous mice, and 9 month-old retired breeders. E2 treatment significantly increased lipid peroxidation, protein carbonylation, and protein nitrosylation in the virgin mice, but not in the age-matched primiparous mice or retired breeders. Mammary gland expression of the oxidative stress response protein Cu/Zn superoxide dismutase was consistently reduced in all of the E2-treated mice regardless of parity. Expression of the oxidative stress and DNA repair protein apurinic endonuclease (Ape1) was significantly increased only in the mammary glands of the E2-treated retired breeders. These findings suggest that E2 and parity help to reduce mammary oncogenesis by maintaining the structure and function of proteins, lipids, and DNA. Highlights: Parity protects the mammary gland from E2-mediated protein and lipid damage. E2 decreases expression of superoxide dismutase in the mouse mammary gland regardless of parity. E2 increases apurinic endonuclease expression in the mammary glands of retired breeders. E2 and parity help protect the mammary gland by reducing damage to cellular macromolecules.